Theory Research in India: 2019–2022. - AISWARYA, C.; ARVIND, V.; SAURABH, SAKET (Communications of the ACM, 2022)
This article explores the trends in computer science research in India from 2019 to 2022 based on research coming out of leading Indian technology institutes, including Chennai Mathematical Institute, Indian Institute of Science and Indian Institute of Technology Delhi. Topics include research on automata theory, formal verification, computational complexity research, and Algorithms research.